2022
DOI: 10.3390/nu14153191
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and its Association with Nutritional Status, Cardiometabolic Risk Factors and Food Choices of Adults at Risk for Type 2 Diabetes Mellitus in Cape Town, South Africa

Abstract: In South Africa, the nutrition transition has led to unhealthy diets lacking variety, contributing to the rise in overweight, obesity and diet-related noncommunicable diseases. Using baseline screening data of the South African Diabetes Prevention Programme (SA-DPP) study, this study aims to determine the relationship of dietary diversity (DD) with nutritional status, cardiometabolic risk factors and food choices of adults at risk of type 2 diabetes in resource-poor communities around Cape Town. Data of 693 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…In this study, DDS also had a negative association with the TG level. This association is consistent with the findings of previous studies in different settings ( 16 , 48 , 49 ). A study among older people residing in a rehabilitation centre found a negative association between DDS and TG levels ( 48 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, DDS also had a negative association with the TG level. This association is consistent with the findings of previous studies in different settings ( 16 , 48 , 49 ). A study among older people residing in a rehabilitation centre found a negative association between DDS and TG levels ( 48 ).…”
Section: Discussionsupporting
confidence: 93%
“…A study among older people residing in a rehabilitation centre found a negative association between DDS and TG levels (48). This association is also observed in people with at risk of diabetes or pre-diabetes (16,49). However, the prior study conducted among Han and Tibetan older highlanders in China reveals a different conclusion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is very worrying because DDS is an indicator of macro and micro nutrients sufficiency, which is required for optimal growth and good health. 27 From Madlala et al, 40 There was significant association between knowledge in nutrition and all body composition parameters; body fat (p = 0.004), BMI (p = 0.001), and WHR (p < 0.001), and visceral fat (p = 0.008). Brien and Davies 43 presented no significant correlation between levels of knowledge and BMI, Yahia et al 44 presented a negative correlation between NK and fat and cholesterol intake.…”
Section: Discussionmentioning
confidence: 93%
“…Most individuals diagnosed with CMDs also experience additional cardiometabolic risks, including obesity, dyslipidemia, hyperinsulinemia, and thrombosis [2]. Unhealthy diets and accelerated population aging have resulted in an annual increase in the prevalence and mortality of CMDs, which places a significant economic burden on the healthcare systems of various countries [3,4]. Studies have shown that these metabolic disorders may be influenced by nutrition.…”
Section: Introductionmentioning
confidence: 99%